Edukacja matematyczna małego dziecka w wychowaniu przedszkolnym i nauczaniu początkowym z perspektywy czterdziestolecia Katedry Pedagogiki Wczesnoszkolnej i Pedagogiki Mediów Uniwersytetu Śląskiego w Katowicach - Polewczyk, Irena; Kawiak, Ewelina (Chowanna, 2019)
The aim of the article is to present the achievements of the employees of the Department of Early Childhood Education and Media Pedagogy in mathematical education over forty years of its functioning.. Mathematics is a particularly important area of teaching a young child, which builds the basis for later education and largely determines its success or failure. It is a subject that is difficult by its very nature, and its hierarchical structure means that each element must be well mastered. That is why it is so important to train the teachers of kindergarten and primary education so that they can build a good basis for teaching this subject.